The Effect of Raw Material Costs and Direct Labor Costs on the Cost of Goods Manufactured: Evidence from 3 Putri Coffee Roasting Business in Bumi Agung Village (2023–2025) - Winda Fatrisia; Elvera Elvera; Nurlela Nurlela (The Future of Education Journal, 2026)
Praise and gratitude the author prays to the presence of Allah SWT, because by His grace and blessings this research can be completed properly. This study is entitled “The Effect of Raw Material Costs and Direct Labor Costs on the Cost of Production at Roasting Kopi 3 Putri Business in Bumi Agung Village for the Period 2023–2025”. This study aims to determine the effect of raw material costs and direct labor costs on the cost of production both partially and simultaneously. The research method used is a quantitative method with an associative approach. The population in this study consisted of all reports of raw material costs, direct labor costs, and cost of production at Roasting Kopi 3 Putri Business during the 2023–2025 period, totaling 36 monthly reports. The sampling technique used was saturated sampling, so the entire population was used as the research sample. Data collection techniques were carried out through observation, interviews, documentation, and literature study. Data analysis methods used included normality test, classical assumption test, multiple linear regression analysis, coefficient of determination (R²), t-test, and F-test with the help of the SPSS program. The results of the study indicate that raw material costs and direct labor costs affect the cost of production both partially and simultaneously. Raw material costs have a more dominant influence on the cost of production compared to direct labor costs. The higher the raw material costs and direct labor costs, the higher the cost of production at Roasting Kopi 3 Putri Business in Bumi Agung Village.